Оптимізація руху інформаційних ресурсів установи методом інформаційного моделювання - Романишин, Юлія (Видавництво Львівської політехніки, 2016)
The developed model of movement of information resources gave the possibility to define advantages and drawbacks of information resources functioning in the analized organization. It is offered the means of improving working with information resources. There are information model in database form and e-register of information resources.
Keywords: бази даних; інформаційний потік; інформаційний ресурс; інформаційне моделювання; модель